Awakening dormant glycosyltransferases in CHO cells with CRISPRa - Karottki, Karen Julie la Cour; Hefzi, Hooman; Xiong, Kai; Shamie, Isaac; Hansen, Anders Holmgaard; Li, Songyuan; Pedersen, Lasse Ebdrup; Li, Shangzhong; Lee, Jae Seong; Lee, Gyun Min; Kildegaard, Helene Faustrup; Lewis, Nathan E. (Biotechnology and Bioengineering, 2020)
Chinese hamster ovary (CHO) cells are the preferred workhorse for the biopharmaceutical industry, and CRISPR/Cas9 has proven powerful for generating targeted gene perturbations in CHO cells. Here, we expand the CRISPR engineering toolbox with CRISPR activation (CRISPRa) to increase transcription of endogenous genes. We successfully increased transcription of Mgat3 and St6gal1, and verified their activity on a functional level by subsequently detecting that the appropriate glycan structures were produced. This study demonstrates that CRISPRa can make targeted alterations of CHO cells for desired phenotypes.
Keywords: Biopharmaceutical industry; Chinese Hamster ovary cells; CRISPRa; Functional levels; Glycan structures; Glycosyltransferases; Mgat3; St6gal1; Animals; CHO Cells; Cricetinae; Cricetulus; CRISPR-Cas Systems; Gene Editing; Glycosylation; Glycosyltransferases; Phenotype; Polysaccharides; CHO; CRISPRa; glycosylation; Mgat3; St6gal1